0215 Internationalising signaal: the european chance in occupational health vigilance – proposal for the spanish version. (21st August 2017) - Foresti, Chiara; Lenderink, Annet; Mattioli, Stefano; Godderis, Lode; Beltran, Ana; Serra, Consol
Abstract : Introduction: SIGNAAL is an online non-compensation-based sentinel system to notify possibly new work-related diseases[1]. It is in place since July 2013 in the Netherlands and Belgium and currently in pilot phase in Italy. Through SIGNAAL physicians report diseases they suspect to be work-related: experts assess them identifying possible new occupational health risks. Our aim is to develop the Spanish SIGNAAL to detect these new risks in Spain[1, 2]. Methods: Every part of the online tool will be translated and adapted. The online platform will be developed. A separate team of Spanish assessors within the Occupational Diseases Unit (UPL) of Barcelona will be trained to asses cases reported to the system. SIGNAAL will be promoted through publications, conferences and advertising. Results: Expected Spanish cases will be assessed within the Spanish SIGNAAL. Costs: periodically presented to assess feasibility and acceptability; effectiveness: evaluated in helping the Public Health System to obtain diseases recognition as occupational (and to claim for them); data usage: for informing policy and preventive measures, at a company level but also involving Public Health stakeholders[3, 4]; spreading: progress reports and publications in peer-reviewed journals[4, 5]. By August 2017 the Spanish SIGNAAL will be in pilot phase, so its first results can be presented with examples and encountered pitfalls[5]. Conclusions: An online reporting system within the occupational health framework can provide valuable data on new occupational health risks, especially while using the same tool in several countries to produce comparable information. Internationalising SIGNAAL is a first step to promote Occupational Health Vigilance across Europe[2, 6].